2009
DOI: 10.1080/02841850802637808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gadolinium contrast agents in naïve and nephrectomized rats: Relevance to nephrogenic systemic fibrosis

Abstract: The visible skin lesions seen in this study appeared to be caused by excessive scratching in response to pruritus. As there was no evidence of dermal fibrosis, the cardinal feature of human NSF, this did not appear to be a model of human NSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 19 publications
(31 reference statements)
2
34
1
Order By: Relevance
“…The rats showed increased dermal cellularity composed of dendritic-like cells and spindle-shaped fibrocytes (probably fibroblasts) (11,13) similar to those observed in human NSF patients (5). In a different rat study, skin lesions seen after Omniscan and gadodiamide (Omniscan without excess ligand) treatment were attributed to excessive scratching rather than an NSF-like disease process (23). This hypothesis seems unlikely since, in several studies, the increased cellularity but also the infiltration of CD34-positive was also observed after GBCAs injection in animals without ulcerations (11)(12)(13)24).…”
Section: Nsf Animal Modelsmentioning
confidence: 77%
“…The rats showed increased dermal cellularity composed of dendritic-like cells and spindle-shaped fibrocytes (probably fibroblasts) (11,13) similar to those observed in human NSF patients (5). In a different rat study, skin lesions seen after Omniscan and gadodiamide (Omniscan without excess ligand) treatment were attributed to excessive scratching rather than an NSF-like disease process (23). This hypothesis seems unlikely since, in several studies, the increased cellularity but also the infiltration of CD34-positive was also observed after GBCAs injection in animals without ulcerations (11)(12)(13)24).…”
Section: Nsf Animal Modelsmentioning
confidence: 77%
“…Most non-clinical and clinical studies available to date favour a causal role of dissociated Gd in tissues in the pathogenesis of NSF (Abraham et al, 2008;Fretellier et al, 2011bFretellier et al, , 2012Fretellier et al, , 2013Haylor et al, 2012;Idée et al, 2014;Pietsch et al, 2009;Sieber et al, 2008a,b,c;Wadas et al, 2010), although this hypothesis remains disputed by some authors (Grant et al, 2009;Wermuth and Jimenez, 2014). Basically, GCs differ in their ability to release dissociated Gd, with macrocyclic GCs being kinetically more stable than linear agents and linear ionic compounds being thermodynamically more stable than linear non-ionic GCs (Port et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Interestingly, the NSF-like skin lesions were observed in the animals with the highest gadolinium concentration in the skin (66). The relevance of these models was challenged in a study carried out in naïve and 5/6 nephrectomized rats receiving very high doses of GC (up to 10 mmol/kg of Gd-DTPA-BMA) (67). The authors suggested that skin lesions found in Gd-DTPA-BMA-treated animals were caused by Gd-DTPA-BMA-specific intensive pruritus and scratching.…”
Section: Inertia Of Gadolinium Chelates: Biological Studiesmentioning
confidence: 99%